90 dni spokoju [plakat] . 90 days of peace. Poster (Polska, 1981)
B&w print on white paper. Poster, issued on the occasion of the so called Bydgoszcz Provocation in March 1981, when Solidarity representatives Jan Rulewski, Marian Łabentowicz (on the photographs) and Michał Bartoszcze among others were beaten by the militia. The title refers to the words of general Wojciech Jaruzelski.